Computational Thinking and Learning Disabilities: A Systematic Review - Veiga, Júlia; Aquini, Lui; Pereira, Kayara; Cavalheiro, Simone; Foss, Luciana; Rosa Junior, Leomar da; Jurgina, Laura; Tavares, Tatiana; Pernas, Ana (Anais do Workshop sobre Educação em Computação (WEI), 2025)
This paper presents a systematic literature review on how computational thinking is approached for individuals with learning disabilities, focusing on dyslexia, autism spectrum disorder, and attention-deficit/hyperactivity disorder. The findings emphasize benefits such as enhanced cognitive skills, increased engagement, autonomy in problem-solving, and improved concept retention. However, gaps remain, including a lack of conceptual clarity around computational thinking; the absence of consensus on assessment methods within the analyzed studies, varying evaluation approaches depending on the teaching strategies used; and a scarcity of studies on specific disabilities like dyscalculia.